Yield estimation of North Korean underground nuclear tests using Lg-wave source spectra - Lu, Yu; Zhao, Lian-Feng; Pang, Xin-Liang; Yao, Zhen-Xing (Frontiers in Earth Science, 2024)
In seismic nuclear monitoring, attenuation models are important prerequisites for reliably estimating the explosive yield in an uncalibrated region without the occurrence of standard events. The seismic moment obtained by fitting source spectra is related to the source energy. This approach is appropriate for estimating yield, as the attenuation effects on the propagation path can be accurately considered. In this study, we collected 2022 vertical component waveforms in and around the Korean Peninsula from May 2010 to May 2022 to construct a high-resolution broadband Lg-wave attenuation model and inverted the Lg-wave source excitation spectra of the nuclear explosion simultaneously with attenuation correction. We obtained the scalar seismic moments by fitting the theoretical source spectra based on the Brune (1970) model. Under the given emplacement conditions and burial depths, the seismic moments can be used to estimate yields of the North Korean nuclear tests, which are 4.6, 8.5, 19.9, 20.9, 24.7, and 337.4 kt for six nuclear explosions that occurred between 2006 and 2017. Our results are consistent with those obtained from previous teleseismic observations.